Prenatal Education in the Lontar Anggastyaprana Text the Concept of Fetal Character Formation from a Hindu Perspective - I Nyoman Alit; IG Agung Jaya Suryawan; I Wayan Gata (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the concept of prenatal education within the ancient Lontar Anggastyaprana manuscript to understand character and spiritual formation from the womb. Employing a hermeneutic approach to interpret the Old Javanese and Balinese text, the research identifies five core dimensions of Hindu prenatal education: (1) purification of the seed (sukla-swanita) through marriage ceremonies (pawiwahan); (2) spiritual rituals during pregnancy, including mantras, ngidam, and panglukatan bobotan; (3) the role of Kanda Pat as a medium for spiritual growth; (4) the sacredness of fetal organ formation; and (5) the internalization of sacred syllables (Dasaksara) for spiritual intelligence. The manuscript demonstrates that Hindu prenatal education integrates physical and metaphysical dimensions, placing the divine at the center of early character formation. These findings highlight the need to revitalize traditional manuscript values to support contemporary character education.